Philippine medical thesaurus on diseases skin and connective tissue diseases and neonatal diseases and abnormalities, in Tagalog - Chavez, Loren G.; Quiros, Edgardo B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2002)
The field of medicine is always associated with diseases and abnormalities. Medical terms are largely focused on foreign languages, especially American English, in describing and naming majority of ailments and medical operations. The consequence is that common people cannot completely comprehend medical terms regarding diseases they may have acquired or heard.
With this, the study attempted to translate medical terms in English to Tagalog and constructed a thesaurus. The researcher focused on skin and connective tissue diseases and neonatal diseases and abnormalities subcategories, two of the 24 subcategories of "Diseases" provided in the Medical subject Headings (MeSH 2003).The terms used were from the Medical Subject Headings. One hundred twenty-one (121) terms were successfully translated from the said list and were analyzed using domain analysis. Included were scope notes and relationships between terms were established. Current procedures, medical professionals, linguistic experts and non-medical first language speakers of Tagalog have been important factors in the search for correct and valid equivalent terms in Tagalog and term pronunciations.
The study also captured the pronunciation of translated terms into an audiocassette recorder and stored in compact disc.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings -- Medicine -- Philippines; Skin -- Diseases; Infants -- Diseases; Tagalog language -- Medical Tagalog